Walking the talk? Firm emissions and disclosure during the third phase of the EU emissions trading system - Erik Grenestam (Danmarks Nationalbank, 2022)
I document trends in emissions and emission disclosure for a sample of 141 large firms that were active within the EU Emissions Trading System during its third phase (2013-2019). Using text from annual reports, I document a rising share of emissions-related information. However, my measure of emissions talk is generally not predictive of past or future changes in firm emissions. While scope 1 emissions decreased during the period, the decrease is entirely driven by the utility sector. I also find that, in general, firms that receive a larger share of their emission allowances for free tended to do worse in terms of reducing emissions. Finally, I find no evidence of emissions leakage during the sample period in spite of a shrinking emissions cap and a rise in the price of emission allowances.
Keywords: Q56; Q58; 330; Climate; Financial stability